Health Information Systems (HIS) Implementation As A Contributing Factor To Healthcare Quality In A Private Hospital - Kyongo, Angela (My University, 2021)
This is a study focusing on Health information systems (HIS) implementation as a contributing factor to healthcare quality in a private hospital. This was a cross sectional study utilizing quantitative research approaches. The researcher sought for approval from the Ethics Committee of the hospital under study and ensured confidentiality and anonymity of the collected information.
Keywords: Health Information Systems; patient safety; healthcare quality